2020
DOI: 10.1021/acsomega.0c02124
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Kluyveromyces marxianus Strain QKM-4 and Evidence of Its Volatilome Production and Binding Potentialities in the Biocontrol of Toxigenic Fungi and Their Mycotoxins

Abstract: To overcome the economic losses associated with fungi and their toxic metabolites, environmentally safe and efficient approaches are needed. To this end, biological control using yeasts and safe bacterial strains and their products are being explored to replace synthetic fungicides. In the present study, the biocontrol effect of a yeast strain of Kluyveromyces marxianus , QKM-4, against the growth and mycotoxin synthesis potential of key toxigenic fungi was evaluated. In vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…These values were significantly lower than the control, whereas at days 3, 5 and 7 the diameters were 32.5 ± 0.9 mm, 35.0 ± 1.0 mm and 40.0 ± 1.2 mm, respectively (Figures 2 and 3A). In line with these findings, diameters of A. flavus [23,25] and A. carbonarius [40] colonies were significantly reduced on exposure to yeast VOC. The biocontrol activity of the yeast VOCs is attributed to the release of different antifungal compounds, mainly 2-phenylethanol, which is known to inhibit the growth of fungi even at very low concentrations [41].…”
Section: Effects Of Cyberlindnera Jadinii 273 Volatiles On Fungal Growthsupporting
confidence: 79%
See 2 more Smart Citations
“…These values were significantly lower than the control, whereas at days 3, 5 and 7 the diameters were 32.5 ± 0.9 mm, 35.0 ± 1.0 mm and 40.0 ± 1.2 mm, respectively (Figures 2 and 3A). In line with these findings, diameters of A. flavus [23,25] and A. carbonarius [40] colonies were significantly reduced on exposure to yeast VOC. The biocontrol activity of the yeast VOCs is attributed to the release of different antifungal compounds, mainly 2-phenylethanol, which is known to inhibit the growth of fungi even at very low concentrations [41].…”
Section: Effects Of Cyberlindnera Jadinii 273 Volatiles On Fungal Growthsupporting
confidence: 79%
“…Additionally, the VOCs of Lachancea thermotolerans inhibited the germination and spread of F. oxysporum spores inoculated on tomato leaf surfaces [23]. In another study [25], a yeast, Kluyveromyces marxianus QKM-4, isolated from a local dairy product (laban), inhibited several fungal species from the genera Aspergillus, Penicillium and Fusarium. Moreover, this strain was able to inhibit OTA synthesis by A. carbonarius and P. verrucosum by 98.7% and 99.6%, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our previous studies, we have reported yeast and bacterial cultures possessing strong antifungal potential against toxigenic fungi. This study was designed to investigate in vitro as well as in vivo effects of Bacillus megaterium (BM344-1) against the growth and toxin production potential of toxigenic isolates of A.…”
Section: Introductionmentioning
confidence: 99%
“…Nine yeast isolates were carefully chosen, among those Pichia anomola as a biocontrol agent significantly reduced the progressive growth of Colletotrichum gloeosporioides with inhibition percentage of 79.63% and combination treatment of T. harianum and Pichia anomola , found to inhibit 93.22% of disease [56] . Fusarium species are one of the major contaminants found in the cereals [ 57 , 58 , 59 ].The biocontrol yeast Kluyveromyces marxianus QKM-4 showed the significant drop in the growth of fungal species of Aspergillus, Penicillium and Fusarium genera by the VOC production and percentage of reduction of OTA biosynthesis is 99.6% for Penicillium verecosum and 98.7% for A. carbonarious [60] . The strains of Debaryomyces hansenii , which produce the killer toxins significantly inhibited the fungal pathogen growth of Alternaria brassicola, Alternaria citri, Aspergillus niger and Rhizopus stolonifera as these fungal pathogens are most common causes of post-harvest decays on fruits like apple lemon and tomato [61] .…”
Section: Antifungal Activitymentioning
confidence: 99%